2006
DOI: 10.1093/ajcn/83.1.52
|View full text |Cite
|
Sign up to set email alerts
|

A daily intake of approximately 6 μg vitamin B-12 appears to saturate all the vitamin B-12–related variables in Danish postmenopausal women%

Abstract: A daily vitamin B-12 intake of 6 microg appeared to be sufficient to correct all the vitamin B-12-related variables measured in the postmenopausal Danish women in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 37 publications
4
70
1
1
Order By: Relevance
“…The lower one was established by Valente et al [22] by using FPIA measurement and the higher one was set by Hvas and Nexo [23], Bor et al [24] and Llody-Wright et al [25] using CPB and ELISA analytical methods, respectively. The principal methodology run was RIA assay (65%) and the corresponding cut-off range was between 35 and 40 pmol/L.…”
Section: Holotranscobalaminmentioning
confidence: 99%
“…The lower one was established by Valente et al [22] by using FPIA measurement and the higher one was set by Hvas and Nexo [23], Bor et al [24] and Llody-Wright et al [25] using CPB and ELISA analytical methods, respectively. The principal methodology run was RIA assay (65%) and the corresponding cut-off range was between 35 and 40 pmol/L.…”
Section: Holotranscobalaminmentioning
confidence: 99%
“…The directly linked macromolecular drugs to vitamin B 12 are susceptible to the degradation within the gastrointestinal tract. In addition, according to the limited uptake capacity of vitamin B 12 (2.4 µg/day for adult) (6), the amount of the therapeutic molecule that can be delivered as conjugate is limited. An attractive solution to overcome theses problems would be the incorporation of drug in nanoparticles coated with vitamin B 12 .…”
Section: Introductionmentioning
confidence: 99%
“…These high doses, which ensure passive absorption (in humans), might be required for elderly with (mild) vitamin B12 deficiency or with absorption problems and are attainable with supplements rather than with food (such as meat and dairy products). It is less certain whether such high doses are also required for a general adult population, as Bor et al (2006) showed that a daily intake of 6 mg was sufficient to normalize all vitamin B12-related variables in 98 Danish postmenopausal women.…”
mentioning
confidence: 99%